EFL Teachers Competence in the Context of English Curriculum 2004: Implications for EFL Teacher Education - Nenden Sri Lengkanawati (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: This is a report of a study which was intended to respond to criticism of the English Curricula used in Indonesia which have been claimed by some as failure to make Indonesian students ready in competing with those from other nations. The study tried to portray EFL teachers competence in West Java and the implications for teacher education. Using a descriptive method, the study investigated proficiency of English teachers in West Java as a tool to assess their readiness in facing the challenge of the implementation of the 2004 English Curriculum and its implication for teacher education. The data concerning teachers proficiency in Listening, Structure, and Reading Comprehension were collected using a TOEFL-equivalent test, while the writing skill was gained through a writing test. Interviews were used to gather information concerning problems faced by the teachers in the implementation of and their perception on the new curriculum. The data were then analyzed, described, and interpreted analytically. It was found that the qualification of the majority of the teachers was not yet at a level of presumably sufficient to implement the 2004 curriculum successfully.